2008
DOI: 10.1016/j.jasms.2007.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of multiply-charged intact protein ions using MALDI TOF-TOF mass spectrometry

Abstract: Top down proteomics in a TOF-TOF instrument was further explored by examining the fragmentation of multiply charged precursors ions generated by matrix-assisted laser desorption ionization. Evaluation of sample preparation conditions allowed selection of solvent/matrix conditions and sample deposition methods to produce sufficiently abundant doubly and triply charged precursor ions for subsequent CID experiments. As previously reported, preferential cleavage was observed at sites C-terminal to acidic residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 52 publications
0
59
0
Order By: Relevance
“…MALDI-TOF-TOF was initially developed for high-throughput tandem mass spectrometry (MS/MS) of peptides of digested proteins (i.e., " bottom-up " proteomics; Washburn et al 2001 , Aebersold andMann 2003 ), but it was quickly demonstrated that small or modest-sized, nondigested protein ions could also be analyzed by MS/MS to allow a topdown proteomic identification (Lin et al 2003, Demirev et al 2005, Liu and Schey 2008, Fagerquist et al 2009. As the ions generated by MALDI are primarily (although not exclusively) singly charged, the fragment ions are also singly charged, which greatly simplifies data interpretation.…”
Section: Maldi-tof-tof-ms/ms and Top-down Identification Of Bacterialmentioning
confidence: 99%
See 2 more Smart Citations
“…MALDI-TOF-TOF was initially developed for high-throughput tandem mass spectrometry (MS/MS) of peptides of digested proteins (i.e., " bottom-up " proteomics; Washburn et al 2001 , Aebersold andMann 2003 ), but it was quickly demonstrated that small or modest-sized, nondigested protein ions could also be analyzed by MS/MS to allow a topdown proteomic identification (Lin et al 2003, Demirev et al 2005, Liu and Schey 2008, Fagerquist et al 2009. As the ions generated by MALDI are primarily (although not exclusively) singly charged, the fragment ions are also singly charged, which greatly simplifies data interpretation.…”
Section: Maldi-tof-tof-ms/ms and Top-down Identification Of Bacterialmentioning
confidence: 99%
“…The fragment ions generated may be sufficient for peptide mass fingerprinting, resulting in a searchable sequence " tag " that, when combined with the mass of the protein, can be used to identify the protein from a database. ISD fragment ions can be further mass-selected and fragmented and the fragment ions analyzed, i.e., MS/MS, using either collision-induced dissociation (CID) (Liu and Schey 2008 ) or laser-induced dissociation (LID) (Spengler 1997, Lin et al 2003, Demirev et al 2005, Fagerquist et al 2009. MS/MS of ISD fragment ions provides further sequence coverage extending to the N-or C-termini.…”
Section: Maldi-tof-tof-ms/ms and Top-down Identification Of Bacterialmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initially developed as a high throughput platform for bottom-up proteomics, MALDI-TOF-TOF instruments are increasingly utilized for top-down proteomic identification of non-digested proteins using either in-source decay (ISD) [28][29][30] or post-source decay (PSD) [31][32][33][34][35][36]. As ISD and PSD occur in different regions of the mass spectrometer there are significant differences in ion fragmentation and polypeptide backbone cleavage.…”
mentioning
confidence: 99%
“…Top-down approaches are extremely important for the accurate determination of protein molecular weights, which can be used together with partial protein sequences to provide a level of understanding that cannot be achieved with one piece of information alone [6]. Furthermore, several researchers have demonstrated the ability to obtain structural information from fragmentation of intact proteins in gas phase [7][8][9][10]. The main advantage of performing MS/MS on an intact protein in this way, is that, the whole sequence is available for analysis, as well as any associated post-translational modifications [9].…”
mentioning
confidence: 99%